Electromagnetic Simulations of a Metamaterial Target for Applications in Particle Accelerators; Charged and Neutral Particles Channeling Phenomena - Vaughan T. Thomas; Karataev P. V. Pavel Vladimirovich; Aryshev A. S. Aleksandr Sergeevich; Antonov V. Vladimir; Soboleva V. V. Veronika Vyacheslavovna (2016, 2016)
Title screen